Adherence to the World Cancer Research Fund/American Institute for Cancer Research recommendations and head and neck cancers risk. (January 2017) - Bravi, Francesca; Polesel, Jerry; Garavello, Werner; Serraino, Diego; Negri, Eva; Franchin, Gianni; La Vecchia, Carlo; Bosetti, Cristina
Abstract: Objectives: The World Cancer Research Fund (WCRF) and the American Institute for Cancer Research (AICR) have proposed eight recommendations for cancer prevention, related to body fatness, diet, and physical activity. Our aim is to evaluate the role of adherence to these recommendations on head and neck cancers risk. Materials and methods: We obtained an overall score including seven of the WCRF/AICR recommendations, and examined its relationship with head and neck cancers risk in two Italian case-control studies including 946 patients with oral cavity and pharyngeal (OCP) cancer and 2492 controls, and 689 patients with laryngeal cancer and 1605 controls. Results: Higher adherence to WCRF/AICR recommendations was associated to a reduced risk of OCP cancer (odds ratio, OR = 0.45, 95% confidence interval, CI: 0.33–0.62 for a score of 4–<5, and OR = 0.32, 95% CI: 0.22–0.49 for a score of ⩾5 as compared to <3). The ORs for laryngeal cancer were 0.68 (95% CI: 0.50–0.92) for a score of 3–<4, 0.39 (95% CI: 0.28–0.55) for a score of 4–<5, and 0.24 (95% CI: 0.15–0.38) for a score of ⩾5. Conclusion: Our study indicates that high adherence to the WCRF/AICR recommendations for cancer prevention is associated with a substantially decreased risk of head and neck cancers.